Proceedings of the Third Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2019
DOI: 10.2991/piceeba-19.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership, Work Motivation and Work Satisfaction on Performance of Employees of Education and Culture Department in Padang Pariaman

Abstract: This study aims to examine the effect of leadership, motivation, and job satisfaction on the performance of education and culture department employees of Padang Pariaman Regency. The sampling technique used is by using the proportional stratified random sampling method. The questionnaire was distributed to 112 employees of the Padang Pariaman District Education and Culture Department. Data were analyzed using Path Analysis and processed with SPSS 16.00. The results show that leadership has a significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
5
1
5
Order By: Relevance
“…Another study, transformational leadership effect on organizational innovation and organizational performance of manufacturing companies (Noruzy et al 2013). However, this is in contrast to the study done by Noviyanti et al (2019) where one of the results showed that direct leadership style has no significant effect on employee performance.…”
Section: Transformational Leadership Style and Organizational Performancecontrasting
confidence: 99%
“…Another study, transformational leadership effect on organizational innovation and organizational performance of manufacturing companies (Noruzy et al 2013). However, this is in contrast to the study done by Noviyanti et al (2019) where one of the results showed that direct leadership style has no significant effect on employee performance.…”
Section: Transformational Leadership Style and Organizational Performancecontrasting
confidence: 99%
“…If a career doesn't provide one with opportunities for upward mobility both in careers and society. It'll never be a firstchoice profession and even if people opted it as their first choice, they would always feel lack of job satisfaction (Noviyanti, Syofyan, & Evanita, 2019). Therefore, it is essential that upward mobility of teachers is ensured through natural and artificial means.…”
Section: Introductionmentioning
confidence: 99%
“…Kepuasan kerja akan tinggi apabila keinginan dan kebutuhan perawat yang menjadi motivasi kerja terpenuhi. Hal ini mendukung penelitian yang dilakukan oleh Rahman et al (2019), Puspa , Noviyanti et al (2019), Andani & Ardana (2020), Sylviana et al (2020)"…”
Section: Tabel 6 Deskripsi Jawaban Responden Terhadap Motivasi Kerjaunclassified